Predicting Financial Well-Being in Millennial Workers: A Test of the Theory of Planned Behavior and the Role of Financial Literacy - Jonathan, Ignatius; Bertuah, Eka (Universitas Airlangga, 2025)
Objective: This study investigates the influence of applying the Theory of Planned Behavior and Financial Literacy on building Financial Well-Being in millennial workers. Design/Methods/Approach: This study used a purposive sampling method. The total number of respondents included in the study was 235, and the respondents were millennial workers who had become permanent employees. Data were analyzed using the Structural Equation Model (SEM). Findings: The findings of this study showed that Financial Literacy has a positive effect on Attitude towards Saving. Financial Literacy also positively affects Financial Behavior and Financial Well-Being, both directly and indirectly. Subjective Norm has a positive impact on Attitude towards Saving, but Subjective Norm has not been proven to affect a person's Financial Behavior. Attitude towards Saving positively affects Financial Behavior and has a full mediation role in mediating Subjective Norm with Financial Behavior. The last results of this study also found a positive relationship between Perceived Behavioral Control and Financial Behavior and between Financial Behavior and Financial Well-Being. Originality/Value: This research contributes to the study of financial well-being, with millennial workers as the primary focus. In addition, while both TPB and financial literacy have been used to predict financial behavior, their combined application to specifically predict the financial well-being of millennial workers offers a nuanced and potentially more comprehensive understanding. Practical/Policy implication: Government agencies are advised to provide financial literacy education to children at an early age so they understand the importance of saving and are wiser in using their money. Thus, financial well-being can be achieved as expected.